Flowpath controls on high‐spatial‐resolution water‐chemistry profiles in headwater streams. Issue 6 (8th June 2021) - Dupas, Rémi; Causse, Jean; Jaffrezic, Anne; Aquilina, Luc; Durand, Patrick
Abstract: Stream water chemistry is routinely measured over time at fixed and sparse sites, which provides a coarse image of spatial variability. Here, we measured nitrate, dissolved organic carbon (DOC) and several chemical proxies for water flowpaths, catchment residence time and biogeochemical transformations, every 50–100 m along 13 km of streams in six agricultural headwater catchments (1.1–3.5km 2 ). The objective was to examine controls on longitudinal nitrate profiles at a high spatial resolution during four seasons: rewetting of the catchments in autumn, winter high‐flow, spring recession and summer low‐flow. Our results showed monotonic trends in longitudinal profiles for nitrate and DOC, which were opposite for the two solutes. Spatial trends in water‐chemistry profiles persisted across seasons, which suggests time‐invariant controls on the spatial variations in concentrations. Four catchments exhibited decreasing nitrate and increasing DOC from upstream to downstream, while two catchments exhibited increasing nitrate and decreasing DOC. These smooth gradients did not reflect a longitudinal land‐use gradient, but rather an increase in the proportion of groundwater inflows when moving downstream, as suggested by the chemical proxies and punctual discharge measurements. Water chemistry also changed abruptly at confluences, at a farm point source and at a localized groundwater inflow zone. Abstract : Smooth gradients reflecting a change in flowpaths when moving downstream.